(E)-N-(Anthracen-9-ylmethylidene)-4-nitroaniline - Geetha, K. (International Union of Crystallography, 2011)
In the title molecule, C(21)H(14)N(2)O(2), the anthracenyl system is approximately planar [maximum deviation = 0.056 (4) Å] and is oriented at a dihedral angle of 73.6 (1)° with respect to the benzene ring. An intramolecular C—H⋯N hydrogen bond generates an S(6) ring motif. The crystal packing is stabilized by C—H⋯π and π–π interactions [centroid–centroid distances of 3.688 (2), 3.656 (1) and 3.716 (2) Å].